2019
DOI: 10.1002/ajmg.a.61288
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic variants in COX4I1 associated with a novel phenotype resembling Leigh syndrome with developmental regression, intellectual disability, and seizures

Abstract: Autosomal recessive COX4I1 deficiency has been previously reported in a single individual with a homozygous pathogenic variant in COX4I1, who presented with short stature, poor weight gain, dysmorphic features, and features of Fanconi anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…COX is an enzyme of the mitochondrial respiratory chain which plays a key role in mitochondrial oxidative phosphorylation through a transfer of electrons from cytochrome c to oxygen, leading to the induction of the proton electrochemical gradient and mitochondrial membrane potential (Li, Park, Deng, & Bai, ). A clinical study has shown that the defective production of COX causes myopathy and Leigh syndrome (Pillai et al, ). Mutation in the human COX4I1 gene induces short stature, poor weight gain, and chromosomal breaks (Abu‐Libdeh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…COX is an enzyme of the mitochondrial respiratory chain which plays a key role in mitochondrial oxidative phosphorylation through a transfer of electrons from cytochrome c to oxygen, leading to the induction of the proton electrochemical gradient and mitochondrial membrane potential (Li, Park, Deng, & Bai, ). A clinical study has shown that the defective production of COX causes myopathy and Leigh syndrome (Pillai et al, ). Mutation in the human COX4I1 gene induces short stature, poor weight gain, and chromosomal breaks (Abu‐Libdeh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In most cell types, COX4I2 expression is induced in hypoxia [203,204], but it is constitutively expressed in pulmonary and pancreatic acinar cells [202,205]. In addition, mutations in the gene encoding the ubiquitous isoform, COX4I1, have also been associated with poor growth and Fanconi anemia [206], and with Leigh-like syndrome [207]. COX5A forms an early subassembly complex with COX4 [186].…”
Section: Mutations In Complex IV Structural Subunitsmentioning
confidence: 99%
“…Mutations in the respective genes have been linked to mitochondrial diseases. While COX4-1 patients [63,64] present, for example, short stature and Leigh-like syndrome, COX5A mutations have been associated with psychomotoric delay, cortical atrophy, or lactic acidemia [65,66]. Although PET117 has been reported as a COX15 interactor [67], it has been also defined as an interactor of the late assembly factor PET100 [48,68].…”
Section: Factors Assisting Early Cox Assembly Stepsmentioning
confidence: 99%